The Powers of North Carolina’s Second Executive: Discovering if the Lieutenant Governor Should be Designated more Power under the Constitution - Brinkley, Ethan C (East Carolina University, 2022)
In the original 1776 North Carolina State Constitution, the executive branch of government was solely comprised of the Governor. It was not until 1868 that the Lieutenant Governor position, along with other executive offices, was added to the branch. The current NC State Constitution today was ratified in 1971 and outlines the powers of the Governor and Lieutenant Governor thoroughly. The designated constitutional powers of the NC Lieutenant Governor include serving as the President of the Senate with the ability to cast tie-breaking votes, serving on the State Board of Education, and most notably, succeeding the Governor upon the death, resignation, or removal from office. These powers are weak in the spectrum of NC government because ties in the Senate and Governor’s leaving office are rare. Additionally, it is important to note that in North Carolina, the Governor and Lieutenant Governor are elected separately and independent from each other, which can possibly result in the two offices representing different parties. I am going to argue that the office of the Lieutenant Governor should be delegated more constitutional powers rather than relying so heavily on the assignment of duties from the General Assembly and Governor. I will conduct research on the election style of the Lieutenant Governor, which additional powers (if any) should be designated to the Lieutenant Governor, and what are other States doing in terms of designating executive powers to their Governor and Lieutenant Governor.
Keywords: Lieutenant Governor; Constitutional Powers; Elections